An invisible thread Christmas story - Schroff, Laura
"This heartfelt story tells the true but unlikely tale of a young woman working in the city and a young boy in desperate need of friendship and guidance. In the short time after they meet, Laura realizes Maurice has never celebrated Christmas, so she opens her heart and her home and sets out to show him how wondrous the holiday is. What she finds through his glowing eyes is that the meaning of the holiday is truly about giving, not getting, as they each discover the magic of Christmas and how one small random act of kindness can truly change a life."--Jacket flap.